IMPROVING STUDENTS ACHIEVEMENT IN VOCABULARY THROUGH LUSTERING TECHNIQUE - Lisda Yuniati Tumanggor; Zainuddin (Universitas Negeri Medan, 2013)
This study attempts to improve students’ vocabulary achievement through Clustering Technique. This study was conducted by using classroom action research. The subject of the research was class VIII-B SMP Katolik Trisakti 2 Medan that consisted of 32 students. The research was conducted in two cycles and each cycle consisted of three meetings. The instruments for collecting data were vocabulary tests for quantitative data and diary notes, observation sheet and questionnaire sheet for qualitative data. Students’ score kept improving in every test. In the first cycle test, the mean of vocabulary score was 64.68. And in the second cycle test, the mean of vocabulary score was 79.85. Based on diary notes, observation sheet and questionnaire sheet, teaching and learning process had done effectively showed the improvement. Every student was studied actively. And from the research can be concluded that Clustering Technique can improve students’ achievement in vocabulary.